The role of glutamate transporter-1 in the acquisition of brain ischaemic tolerance in rats induced by electro-acupuncture pre-treatment. (28th October 2014) - Guo, Zhenzhen; Zhang, Li; Wu, Yi; Li, Mingfen; Yang, Xiaojiao; He, Zhijie; Wu, Zhiyuan; Hu, Yongshan; Jia, Jie
Abstract: Objective : To investigate whether electro-acupuncture can serve as a method of inducing brain ischaemic tolerance (BIT) by encouraging the expression of glutamate transporter-1 (GLT-1) and suppressing the release of glutamate (Glu). Methods : Sprague-Dawley (SD) rats were divided into sham, ischaemia and EA groups. EA was performed on dazhui and baihui acupoints and the rat cerebral ischaemia model was achieved by occluding the middle cerebral artery (MCA) for 2 hours, followed by reperfusion. Dialysate was collected from the striatum in vivo to detect the concentration of Glu and the expression of Glutamate Transporter-1 (GLT-1) was examined. The changes of neurological deficit scores were evaluated at 24 hours after reperfusion, while the infarct volumes of brains were then measured with 2, 3, 5-triphenyltetrazolium chloride (TTC) staining. Results : Compared with the ischaemia group, the concentration of Glu decreased and the expression of GLT-1 increased at most of the detective time points in the EA group; the neurological deficit scores were lower and the infarct volumes were smaller in the EA group. Conclusion : EA can up-regulate the expression of GLT-1 and inhibit the excessive release of Glu in the striatum in the process of subsequent ischaemic-reperfusion brain injury, which may be one of the mechanisms of inducing BIT and, thus, be neuroprotective for early ischaemic brain injury.